تأثير برنامج تدريبي على الحد الأقصى لاستهلاك الأكسجين وبعض عناصر اللياقة البدنية لطالبات المرحلة الإعدادية - إسماعيل، جيهان حامد سيد; خليل، مها خليل محمد; أبو المعاطي، هبة محمد عبدالله (جامعة حلوان - كلية التربية الرياضية للبنات, 2023)
ويهدف البحث إلى معرفة تأثير برنامج تدريبي على كلا من بعض عناصر اللياقة البدنية والحد الأقصى لاستهلاك الأكسجين. يتمثل مجتمع البحث من طالبات الصف الثالث الإعدادي وتم استخدام المنهج التجريبي لمجموعه واحده. توصلت الباحثة إلى النتائج الأتية: ١- وجود فروق دالة إحصائيا بين متوسطات درجات القياسين القبلي والبعدي في الحد الأقصى لاستهلاك الأكسجين. ۲- وجود فروق دالة إحصائيا عند مستوي (٠.٠٥) بين القياسين القبلي والبعدي في بعض عناصر اللياقة البدنية (المرونة - الرشاقة - السرعة). وبالتالي فإن البرنامج المستخدم قيد البحث له تأثير إيجابي في الحد الأقصى لاستهلاك الأكسجين وبعض عناصر اللياقة البدنية. The research aims to develop some elements of physical fitness and improve the maximum oxygen consumption. This is done by designing a program to improve the maximum oxygen consumption. The research community consists of third-year middle school students, and the experimental method was used for one group the researcher reached the following results: 1- There are statistically significant differences between the average scores of the pre- and post-measurements in the maximum oxygen consumption. 2- There are statistically significant differences at the level of (0.05) between the pre and post measurements in some elements of physical fitness (flexibility - agility - speed). Therefore, the program used under research has a positive effect in improving some elements of physical fitness and improving some physiological variables.
Keywords: استهلاك الأكسجين -- اللياقة البدنية -- الصحة الرياضية -- طلبة المرحلة الإعدادية